1972
DOI: 10.1002/cjce.5450500604
|View full text |Cite
|
Sign up to set email alerts
|

Bed expansion in a mobile‐bed contactor

Abstract: The expanded bed height has been investigated in a 0.14-m diameter mobile-bed gas-liquid contactor. The data obtained by two methods of measurement show that the bed height varies linearly with the gas flow rate and is independent of the packing density. The operation of the bed is characterized by the condition of flooding. Correlations are presented for the expanded bed height and the minimum fluidization velocity in terms of the independent system variables.obile-bed contacting is a technique of counter-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Tichy and Douglas investigated variations of minimum fluidisation velocity in TBCs, and developed the empirical model given below to predict U mf in TBCs both for type I and type II operation: Umf=1ρnormalg(0.36355+57.9dnormalP1.848GnormalL0.6dnormalP0.5) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tichy and Douglas investigated variations of minimum fluidisation velocity in TBCs, and developed the empirical model given below to predict U mf in TBCs both for type I and type II operation: Umf=1ρnormalg(0.36355+57.9dnormalP1.848GnormalL0.6dnormalP0.5) …”
Section: Resultsmentioning
confidence: 99%
“…Most correlations omit the gas density since it is negligible with respect to that of the solid. Some of the studies conducted on TBC behaviour have reported pressure drop independence on gas velocity and packing size, whereas others claimed a pressure drop variation with the packing size. However, for small grid open areas, the pressure drop is reported to increase with gas velocity .…”
Section: Theoretical Background Of Tbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Results similar to this on bed expansion have been reported by Chen and Douglas (1969) (1972), and Soundarajan (1995). The experimental data of Tichy and Douglas (1972), Rama et al (1983) and Soundarajan (1995) are compared with model predictions in Fig. 4 (inset).…”
Section: Bed Expansionmentioning
confidence: 98%
“…Preliminary studies on this device were carried out by Douglas and coworkers [5][6][7][8]. O'Neill [9] observed two operating conditions for a TCA; fluidization with preliminary flooding and fluidization without preliminary flooding.…”
Section: Introductionmentioning
confidence: 99%